POR ENTRE AS COLUNAS POLÍTICAS: AS REPRESENTAÇÕES DAS ELEIÇÕES MUNICIPAIS NA IMPRENSA ESCRITA EM PONTA GROSSA -1992/1996/2000 - Anjos, Marcelo Puzio dos (2012)
This Study at analyzing the representations constructed by political columms on the election for mayor, the periods 1992, 1996 and 2000, the city of Ponta Grossa – PR. The research outlined in this sense a configuration colunismo political and discursive strategies of intervention in the political game, can also reveal not only the disputes between the political forces that acted at that moment, but also the changes and continuities of journalistic field site, especially in its zone opinionated.